FINANCIAL AND ORGANIZATIONAL PROBLEMS OF IMPORT SUBSTITUTION IN RUSSIA - O. Makhalina (Вестник университета)
Internal and external theoretical and practical problems of import substitution are considered. The analysis of methods and approaches of scientists and authorities to the solution of these problems is stated, some results of financing of process of import substitution are given, the main proposals of the author, on increase of efficiency of import substitution in the Russian economy are formulated.